The effects of attractive but unattainable alternatives on the attractiveness of near and distant future menus - Leah Borovoi; Nira Liberman; Yaacov Trope (Judgment and Decision Making, 2010)
We examine how adding an Attractive but Unattainable Alternative (AUA) to a set of available but less attractive alternatives influences evaluations of near vs. distant future sets of alternatives. According to Construal Level Theory (Liberman & Trope, 2008) including an AUA would decrease the attractiveness of near future sets, but may increase the attractiveness of distant future sets. In four studies participants imagined a choice situation with three alternatives. For some participants a fourth alternatives was added, which was attractive but unattainable. Half of the participants in each condition imagined making a decision in the near future whereas others imagined making the decision in the distant future. Participants then evaluated the attractiveness of the entire set of alternatives, as well as of each alternative separately. We examined choices between jobs, computers and roommates. The last study examined negotiations with the landlord about an apartment. Consistent with our hypothesis, an AUA increased the evaluation of the distant set and decreased the evaluation of the near set.